Second harmonic generation microscopy probes different states of motor protein interaction in myofibrils - Schürmann, Sebastian; Wegner, Frederic von; Fink, Rainer; Friedrich, Oliver; Vogel, Martin (Biophysical journal, 2010)
The second harmonic generation (SHG) signal intensity sourced from skeletal muscle myosin II strongly depends on the polarization of the incident laser beam relative to the muscle fiber axis. This dependence is related to the second-order susceptibility χ(2), which can be described by a single component ratio γ under generally assumed symmetries. We precisely extracted γ from SHG polarization dependence curves with an extended focal field model. In murine myofibrillar preparations, we have found two distinct polarization dependencies: With the actomyosin system in the rigor state, γrig has a mean value of γrig = 0.52 (SD = 0.04, n = 55); in a relaxed state where myosin is not bound to actin, γrel has a mean value of γrel = 0.24 (SD = 0.07, n = 70). We observed a similar value in an activated state where the myosin power stroke was pharmacologically inhibited using N-benzyl-p-toluene sulfonamide. In summary, different actomyosin states can be visualized noninvasively with SHG microscopy. Specifically, SHG even allows us to distinguish different actin-bound states of myosin II using γ as a parameter.